USE OF SOCIAL MEDIA AS A MEANS OF INFORMATION SERVICES IN GUIDANCE AND COUNSELING - Lisnawati, Lisnawati; Safitri, Anggie Resa; Yasin, M. Aidil; Labibah, Adzra Reva (Jurnal Kopendik, 2024)
This research constitutes a literature review that discusses the utilization of social media as a means of information service in guidance and counseling. In this review, various relevant literature sources are explored to understand the role and impact of social media usage in the context of guidance and counseling. The analysis encompasses the benefits obtained, challenges faced, as well as ethical implications to be considered regarding the utilization of social media in guidance and counseling practices. The findings of this review provide a deeper understanding of the potential of social media as an effective supplementary tool in providing information services in guidance and counseling, while still emphasizing the importance of ethical handling and understanding of its limitations and risks